Labor Demand Responses to Changing Gas Prices - Bossler, Mario; Moog, Alexander; Schank, Thorsten (B E Journal of Economic Analysis & Policy, 2023)
In course of the current energy crisis, the consequences of increasing gas prices are heavily discussed. To date, however, there is no evidence of the impact of gas prices on the labor market. Using administrative employment data from 2012 to 2020, we find for manufacturing establishments a gas price elasticity of labor demand of -0.02, likely reflecting a scale effect. We also show that a rise in the gas price leads to an increase in establishment closure. A negative impact of the gas price on wages of 2 percent is consistent with rent-sharing.
CRIS-Team Scopus Importer:2023-11-10
Keywords: elasticity; establishment closure; gas price; labor demand; wages